Musicians' Creativity in Developing Songs from the '90s to the Present Context (Case Study of Band Diffunex and Ruang Putih) - Avio Ekklesia Yomuda (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2024)
This study explores how musicians innovate in creating songs that combine elements of the ‘90s and current trends through in-depth interviews with the DiffunexBangil Band and the Ruang Putih Gempol Band. Using qualitative research methods, the results show the musicians incorporate new elements into their music while still maintaining the ‘90s vibe, creating a synergy between nostalgia and innovation. Factors driving this creativity include the influence of popular culture, evolving music technology, and the desire to remain relevant in the ever-changing music industry. The aim of this research is to provide new insights into how musicians adapt and innovate in an ever-changing context, and how they use their creativity to bridge the gap between the past and the present. the results of this study describe the information obtained from various sources focusing on (1) The formof creativity of today’s musicians in translating ‘90s music elements into their works, (2) The challenges faced by musicians in trying to incorporate the ‘90s vibe into contemporary music, (3) How musicians use their creativity in preserving the essence of ‘90s music while remaining relevant in the modern music industry.